Group 3 LEA Protein, ZmLEA3, Is Involved in Protection from Low Temperature Stress - Liu, Yang; Liang, Jianan; Sun, Liping; Yang, Xinghong; Li, Dequan (Frontiers in Plant Science, 2016)
Late embryogenesis abundant (LEA) proteins are a family of small highly hydrophilic proteins that accumulate at the onset of seed desiccation and in response to adverse conditions such as drought, salinity, low temperature, or water deficit. In previous studies, we demonstrated that ZmLEA3 could enhance the transgenic tobacco tolerance to osmotic and oxidative stresses. Here, we demonstrated that the transcription of ZmLEA3 in the maize stems could be significantly induced by low temperature and osmotic stresses and by treatment with abscisic acid (ABA) and H2O2. Further study indicated that ZmLEA3 is a single copy gene in the maize genome. The ZmLEA3 protein could protect lactate dehydrogenase (LDH) activity at low temperatures. The overexpression of ZmLEA3 conferred tolerance to low-temperature stress to transgenic tobacco, yeast (GS115) and E. coli (BL21).